C–kit proto-oncogene expression in uterine leiomyosarcomas: case series - VR , Naik; J, Hasnan (IIUM Medical Journal Malaysia, 2008)
Introduction: The proto-oncogene c-kit is the cellular homologue of the oncogene v-kit of HZ4 feline sarcoma virus. It is located on chromosome 4 (4q11-12) in the human genome. Interaction between the c-kit receptor and its ligand, stem cell factor, is essential in the development of tissues. C-kit expression has been identified in a number of different neoplasms like seminoma/dysgerminoma, and gastrointestinal stromal tumors (GIST). Recently it has been reported that c-kit is also present in leiomyosarcomas. Tyrosine kinase inhibitors (TKIs) are a promising new therapy in the treatment of cancer. These agents target cellular proteins like kit and its related homologues decreasing cellular proliferation and survival. TKIs may be helpful in treating leiomyosarcomas expressing c-kit. Materials and Methods: In this study a total of 6 cases diagnosed as leiomyosarcomas at Department of Pathology, Universiti Sains Malaysia, Kubang Kerian, Malaysia, were investigated for reactivity for c-kit using immunohistochemical stain. Stain was considered positive if more than 10 percent of the cells showed membrane or cytoplasmic positivity. Results: Two leiomyosarcomas stained faintly with c-kit and in less than 10 percent of the cells. The other 4 cases showed no staining. The control showed good membrane and cytoplasmic positivity. Conclusion: Uterine leiomyosarcomas did not express c-kit. The reason for this could be that the tumors are inherently c-kit negative. More study using larger number of cases is required to validate these findings and further molecular characterization of these mesenchymal tumors is needed to identify the true nature of these sarcomas.